Energy drinks at adolescence: Awareness or unawareness? - Cadoni, Cristina; Peana, Alessandra Tiziana (Frontiers in Behavioral Neuroscience, 2023)
Energy drinks (EDs) are beverages similar to soft drinks, characterized by high caffeine concentrations with additional ingredients like taurine and vitamins, marketed for boosting energy, reducing tiredness, increasing concentration, and for their ergogenic effect. The majority of consumers are children, adolescents, and young athlete. Although EDs companies claim about the ergogenic and remineralizing properties of their products, there is a serious lack of evidence at preclinical as well as clinical level to validate their benefits. The regular intake and long-term consequences of these caffeinated drinks are not well documented, especially the possible negative effects in adolescents whose brain is still developing. EDs combined with alcohol are also gaining popularity among adolescents and different publications indicate that this combined consumption might increase the risk to develop an alcohol use disorder, as well as produce serious adverse cardiovascular effects. There is an increasing need to disseminate knowledge on EDs damage on health, so that adolescents can be aware about the potential harmful outcomes of consuming these drinks.